Investigation of taxonomically important morphological features of endoparasitic bat flies of the subfamily Ascodipterinae (Diptera: Streblidae) by scanning electron microscopy - Hastriter, Michael W.; Dittmar, Katharina; Whiting, Michael F. (Zootaxa, 2006)
Endoparasitic dealate females of Ascodipteron and an undescribed genus of Ascodipterinae are examined by scanning electron microscopy. The unique morphology of the head and mouth parts and terminal segments are displayed and discussed. Prior reports have focused only on details observable with light microscopy. The taxonomic position of members of the subfamily Ascodipterinae relative to the Old World families of Streblidae and Nycteribiidae is briefly discussed in light of previously published molecular information.